PMT_EDS: Pattern Matching as a Tool for Efficient and Dynamic Search in the Large Files - Hrushikesava Raju, S; Nagabhushana Rao, M (International Journal of Computer Sciences and Engineering, 2025)
There exist many pattern matching approaches, which consume more time and unable to perform operations like recording history, finding number of times a pattern is found along with positions, page numbers etc. and they have limitations in performing operations beyond their usual operations. The pattern matching using indexOf method is proposed to find out a specific pattern or multiple patterns at a time in less time complexity. The additional information is reported by recording history operation, information of where the pattern is located like page number, number of times that pattern is found can be processed by searching operation, and multi-process operation searches multiple patterns and returns their locations, page numbers in less time complexity by using indexOf metod as a thread in achieving better efficiency. To do all these operations, an automated tool is required that asks for operation to perform, required details to be provided in that operation, and results going to be illustrated or reported. Data pre-processing is required when there is any inconsistency present in the dataset.